AFRICA IN INTERNATIONAL RELATION - Dr. Alier,; Ayuel Bill , Dut Bol (IJRDO - Journal of Social Science and Humanities Research, 2022)
THE HISTORICAL PERSPECTIVES OF AFRICAN STATES AND THEIR RELATIONIn the orthodox of understanding of Statehood, Africa entered to the International system at late stages due to colonialism where most African States gained independence. Before that African States provided labour (slavery) and raw materials. The African colonial entities couldn’t be conceived as equal participants in the initiation and implementation of the foreign policies.The Berlin congress petitioned Africa arbitrarily into units, kingdoms, states and communities in the convenience of the colonial masters. However the International Court of Justice decided to rule in fever of the Status quo, in favor of peace, e.g. the ruling of ICC in disputes of Burma and Mali in 19…… In this case, under the ICC, it was found that maintaining the territorial status quo of the International boundaries was the only way of maintaining peace and gaining independence. The next move was the struggle for independence as a means of stability and development, and indeed after the independence, all the African States has consented to the colonial frontiers